Energy conservation theory for second language acquisition (ECT-L2A): a partial validation of kinetic energy–aptitude and motivation - Kim, Peter (Frontiers in Physics, 2023)
While language aptitude and motivation are important contributors to second language (L2) attainment, two major gaps in the past research have been (1) a lack of nonlinear models stemming from a naïve and tacit assumption that learning outcomes are linearly related to their predictors, and (2) a lack of unified and integrative understanding of key individual differences (ID) variables. Despite changes in conceptualization of language development as a dynamic system comprised of nonlinear and interconnected subsystems (e.g., CDST), an integrative understanding of ID variables in L2 acquisition remains lacking. The purpose of this study was to examine motivation and aptitude and their relationship to second language acquisition. Specifically, the study set out to validate a number of theoretical claims made by energy conservation theory for second language acquisition (ECT-L2A) and its attempt to unify key ID variables under one model (Han et al., 2017a). ECT-L2A predicts, inter alia, that aptitude and motivation are positively related to L2 achievement but their effects diminish with increase in proficiency. This is visually represented as a nonlinear and asymptotic L2 learning trajectory vis-à-vis aptitude and motivation. In the current study, two hundred and three adult Spanish-speaking learners of L2 English (N=203) of wide range of proficiency were measured on their level of aptitude (LLAMA_F), motivation (Attitude Motivation Test Battery) and attainment (grammaticality judgment test). The data were analyzed using correlations, R-squared measures, and fitted with orthogonal regression via total least-squares method. The results of correlation analyses and regression showed that as predicted, aptitude contributed positively towards attainment, but its effect diminished with increase in proficiency. On the other hand, while all participants were motivated to learn, motivation decreased with increases in attainment throughout L2 development. Motivation’s effect on achievement became asymptotic and its contribution towards target language (TL) mastery diminished. When aptitude and motivation were combined as a single unit, the learning trajectory closely resembled the curve predicted by ECT-L2A. Based on these findings, two general interpretations concerning motivation and aptitude were presented: 1) changes in motivation and aptitude with respect to attainment and 2) their differential efficacy towards native-like proficiency during L2 development.